Entrepreneurship - Keister, Lisa A., 1968- (Amsterdam ; Boston : Elsevier JAI, 2005)
Entrepreneurship, the creation of new economic entities, is central to the structure and functioning of organizations and economies. New business formation also shapes the nature of social and economic stratification in an economy and may be an important vehicle for social mobility. The papers in this volume explore many of the issues that are central to the study of entrepreneurship today and also break new ground in the field. The papers explore the importance of entrepreneurship, the process by which entrepreneurship occurs, and the way both meaning and process vary with context and opportunity structures.These papers address long-standing controversies in the study of entrepreneurship, and they also identify new, innovative questions and approaches. As a result, both seasoned entrepreneurship researchers and those who are new to the field will find the papers interesting and useful. Research in the Sociology of Work is now available online at ScienceDirect full-text online of volumes 10 onwards.
Entrepreneurship and inequality / Stephen Lippmann, Amy Davis and Howard E. Aldrich -- Economic freedom or self-imposed strife: work-life conflict, gender, and self-employment / Jeremy Reynolds and Linda A. Renzulli -- Origins of organizations: the entrepreneurial process / Martin Ruef -- Technological resources and new firm growth: a comparison of start-up and adolescent ventures / Shaker A. Zahra and Bruce A. Kirchhoff -- Management paradigm change in the United States: a professional autonomy perspective / Bruce C. Skaggs and Kevin T. Leicht -- Upside-down venture capitalists and the transition toward pyramidal firms: inevitable progression, or failed experiment? / Noam Wasserman -- Entrepreneurship, industrial policy, and clusters: the growth of the North Carolina wine industry / R. Saylor Breckenridge and Ian M. Taplin -- Socializing the ethnic market: a frame analysis / Louis Corsino and Maricella Soto -- The henna maker: a Moroccan immigrant woman entrepreneur in an ethnic revival / Beverly Mizrachi -- Entrepreneurship and self-employment in transition economies / Akos Rona-Tas and Matild Sagi -- Entrepreneurial strategies during institutional transitions / Mike W. Peng and Yi Jiang -- Lineage networks, rural entrepreneurs, and Max Weber / Yusheng Peng.
Description based on print version record.
Keywords: Entrepreneurship; Sociology: work & labour; Business & Economics -- Entrepreneurship